Legal Literacy Strengthening for Indonesian Migrant Workers: Self-Help Ability to Survive the Life - Vera Bararah Barid; Sri Wahyu Kridasakti; Purwaningdyah Murti Wahyuni (Universitas Lampung, 2022)
Indonesian migrant workers are foreign exchange heroes, and their presence can get better welfare for their families and surrounding communities. However, the state's contribution to Indonesian migrant workers is still not maximized. It can be seen in several cases faced by Indonesian migrant workers in destination countries. One of the main factors causing various legal problems faced by migrant workers is the lack of knowledge and skills in the practical field of law related to their work and work environment. This paper will discuss legal literacy as the determinant factor to be mastered by Indonesian migrant workers to survive working in other countries. This socio-legal research uses a qualitative approach; the data used are primary that have been collected for the last three years (2020-2022, and secondary data. Primary data is based on survey results (2020) and FGDs with experts conducted in the previous three years. The secondary data comes from journals, books, reports, and other related articles. This paper concludes that the distance education and learning platform with continuing education (non-degree) service format is the most suitable and efficient design for providing access to education for migrant workers to survive their life in overseas.